Antifungal activity and mechanism of Phoebe bournei wood essential oil against two dermatophytes - Yang, Yan; Sun, Qinglin; Zhang, Yuting; Huang, Junhua; Ma, Wenjun; Yang, Qi; Tong, Zaikang; Zhang, Junhong (Frontiers in Microbiology, 2025)
BackgroundDermatophytes are notorious pathogenic fungi that threaten human health and reduce quality of life. Phoebe bournei (Hemsl.) Yen C. Yang wood essential oil (PWEO) has been found to have excellent antifungal activity, but its mechanism remains unclear.MethodologyDetermination of minimum inhibitory concentration (MIC) of PWEO on two dermatophytes (Microsporum gypseum and Epidermophyton floccosum) by broth microdilution method. Culture plates containing PWEO in vitro tested PWEO inhibition effect of mycelial growth of dermatophytes and the effect of PWEO on hyphal structure was observed by microscopy; the changes of cell membrane permeability and the degree of lipid peroxidation were reflected by measuring cell physiological indexes. ROS and MMP probe detection of intracellular ROS and MMP change. Finally, WGCNA analysis was used to identify and verify the key genes.ResultsWe found that the main components of PWEO are monoterpenes and sesquiterpenoids. The PWEO had strong antifungal activity, and the MIC of PWEO against both dermatophytes was 3.600 mg/mL. PWEO significantly inhibit mycelial growth, and the inhibitory effect increases significantly with increasing concentration. When the PWEO concentration reaches 1.8mg/mL, mycelial growth is completely inhibited. Microscopic observation showed that PWEO destroy the structure of hyphae. The cell membrane permeability test indicated that the cell membrane of dermatophytes was damaged by PWEO. Cellular malondialdehyde (MDA) content was positively correlated with the concentration of PWEO, suggesting that lipid peroxidation of dermatophytes was caused by PWEO. Fluorescence microscopy images showed excessive production of ROS and disruption of MMP in dermatophytes after PWEO treatment. Physiological experiment of M. gypseum showed significant differences in protein extravasation, extracellular conductivity and intracellular MDA content after three hours of treatment with 0.450 mg/mL PWEO compared with the control. Five hub genes were identified by weighted gene co-expression network analysis (WGCNA), of which Long chain fatty acid CoA ligase 1 (ACSL1) was significantly up-regulated expressed. Meiotically up-regulated 72 (MUG72) and GDP-mannose transporters gene 1 (GMT1) were significantly down-regulated expressed after PWEO treatment, which affected the growth and reproduction of M. gypseum. These results suggest that PWEO can be used as natural antifungal agents for sustainable applications.